Phaon Crescent, Mat Plant Crescent, Physiodes phaon (Edwards) (Insecta: Lepidoptera: Nymphalidae) - Donald W. Hall; Jerry F. Butler (EDIS)
The phaon crescent is a common southern crescent that frequents moist open areas. It resembles the pearl crescent that is found in the same areas, but differs by the more checkered fringe on the wings. This document is EENY-109, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1999. Reviewed May 2003.